State-Level Health and Economic Impact of COVID-19 in India - Deb, Pragyan; Xu, TengTeng (Washington, D.C. : International Monetary Fund, 2021)
The health and economic impacts of COVID-19 on India have been substantial, with wide variation across states and union territories. This paper quantifies the impact of containment measures and voluntary social distancing on both the spread of the virus and the economy at the state level during the first wave of the COVID-19 pandemic. We construct a de-facto measure of state-level social distancing, combining containment strigency and observed mobility trends. State-level empirical analysis suggests that social distancing and containment measures effectively reduced case numbers, but came with high economic costs. State characteristics, such as health care infrastructure and the share of services in the economy, played an important role in shaping the health and economic outcomes, highlighting the importance of adequate social spending, health care infrastructure, and social safety nets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Containment Measures; COVID-19; Multiple or Simultaneous Equation Models; Social Distancing; Studies of Particular Policy Episodes